Mixed C-Cosine of Continuous Linear Operators on Complex p-Banach Spaces - Jawad Ettayb (Pan-American Journal of Mathematics, 2025)
In the present work, we define and examine the mixed C-cosine families of continuous linear operators on complex p-Banach spaces where 0 p 1. Finally, we will demonstrate several results on the mixed C-cosine families of continuous linear operators on complex p-Banach spaces where 0 p 1. Finally, we give an application related to the second order abstract Cauchy problem.